Method for producing positive electrode active material for lithium secondary battery

By calcining the raw materials of the positive electrode active material of the lithium-ion battery at high temperature, the problem of degradation of the cycle characteristics of the positive electrode active material of the lithium-ion battery is solved, and the excellent cycle characteristics and longer service life of the battery are achieved.

JP2025064405APending Publication Date: 2025-04-17NIPPON CHEMICAL IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023174153
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-06
Publication Date
2025-04-17

AI Technical Summary

Technical Problem

Existing lithium-ion batteries use lithium-nickel yttrium calcium composite oxide as the positive electrode active material. Although there are improvements in cost and capacity, their cycle characteristics still have deterioration problems.

Method used

By mixing a nickel source, manganese source, cobalt source, lithium source, lithium tungstate acid and necessary M source, and performing high-temperature calcining treatment, a positive electrode active material with excellent circulation characteristics was prepared.

Benefits of technology

This method can significantly improve the circulation characteristics of lithium-ion batteries, extend the service life of the battery, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025064405000005
    Figure 2025064405000005
  • Figure 2025064405000006
    Figure 2025064405000006
  • Figure 2025064405000007
    Figure 2025064405000007
Patent Text Reader

Abstract

To provide a method for producing a positive electrode active material for a lithium secondary battery, capable of imparting excellent cycle characteristics to a lithium secondary battery using a lithium nickel manganese cobalt composite oxide as a positive electrode active material.SOLUTION: A method for producing a positive electrode active material for a lithium secondary battery comprises firing a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and optionally an M source.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]

[0002] Conventionally, lithium cobalt oxide has been used as a positive electrode active material for lithium secondary batteries. However, since cobalt is a rare metal, lithium nickel manganese cobalt composite oxides with a low cobalt content have been developed (for example, see Patent Documents 1 and 2).

[0003] It is known that lithium secondary batteries that use a lithium nickel manganese cobalt composite oxide as a positive electrode active material can reduce costs by adjusting the atomic ratio of nickel, manganese, and cobalt contained in the composite oxide, and also have a higher capacity than lithium cobalt oxide (see, for example, Patent Document 3).

[0004] However, even with these conventional techniques, the lithium secondary battery using the lithium nickel manganese cobalt composite oxide as the positive electrode active material still has the problem of deterioration of cycle characteristics.

[0005] As a method for improving the cycle characteristics of a lithium secondary battery using a lithium nickel manganese cobalt composite oxide as a positive electrode active material, a method of coating the particle surface of the lithium nickel manganese cobalt composite oxide with a Ti-containing compound has been proposed (see, for example, Patent Document 4 and Patent Document 5). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2004 / 092073 Brochure [Patent Document 2] JP 2005-25975 A [Patent Document 3] JP 2011-23120 A [Patent Document 4] JP 2016-24968 A [Patent Document 5] JP 2016-72071 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, lithium secondary batteries have been considered for use in the field of automobiles, such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles. For this reason, there is a demand for further improvement in the cycle characteristics of lithium secondary batteries that use lithium nickel manganese cobalt composite oxide as the positive electrode active material.

[0008] Therefore, an object of the present invention is to provide a method for producing a positive electrode active material for a lithium secondary battery, which can impart excellent cycle characteristics to a lithium secondary battery using a lithium nickel manganese cobalt composite oxide as a positive electrode active material. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive research in light of the above-mentioned circumstances and have found that a positive electrode active material for lithium secondary batteries having excellent cycle characteristics can be obtained by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and, as necessary, an M source to obtain a raw material mixture, and firing the raw material mixture at a predetermined temperature, thereby completing the present invention.

[0010] That is, the present invention (1) provides a method for producing a positive electrode active material for a lithium secondary battery, characterized by calcining a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and, as necessary, an M source.

[0011] The present invention (2) also provides a method for producing a positive electrode active material for a lithium secondary battery according to (1), characterized in that a composite compound containing nickel atoms, manganese atoms, and cobalt atoms is used as the nickel source, the manganese source, and the cobalt source.

[0012] The present invention (3) also provides the method for producing a positive electrode active material for a lithium secondary battery according to (1) or (2), characterized in that the lithium tungstate is Li2WO4.

[0013] The present invention (4) also provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (1) to (3), characterized in that the material is fired at 600 to 1000°C.

[0014] The present invention (5) also provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (1) to (4), characterized by calcining at 600 to 800°C for 1 to 10 hours, and then calcining at 800 to 1,000°C for 5 to 30 hours.

[0015] The present invention (6) also provides the method for producing a positive electrode active material for a lithium secondary battery according to any one of (1) to (5), characterized in that the amount of lithium tungstate mixed is an amount such that the amount of W, calculated as an atom, is 0.01 to 5.00 mol % relative to the total amounts of Ni, Mn, Co, and M, calculated as atoms, in the nickel source, manganese source, cobalt source, and M source.

[0016] The present invention (7) also provides a positive electrode active material for a lithium secondary battery, comprising: Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y satisfies 0.30 ≦ y < 1.00, z satisfies 0 < z ≦ 0.50, t satisfies 0 < t ≦ 0.50, p satisfies 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) It is characterized by including lithium nickel manganese cobalt composite oxide particles represented by and W atoms, and provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (1) to (6).

[0017] Further, the present invention (8) provides a method for producing a positive electrode active material for a lithium secondary battery, which includes a step of mixing large particles having an average particle diameter of 7.5 to 30.0 μm obtained by any one of the production methods of (1) to (7) and small particles having an average particle diameter of 0.5 to 7.5 μm obtained by any one of the production methods of (1) to (7).

Effects of the Invention

[0018] According to the present invention, it is possible to provide a method for producing a positive electrode active material for a lithium secondary battery that can impart excellent cycle characteristics to a lithium secondary battery using a lithium nickel manganese cobalt composite oxide as a positive electrode active material.

Brief Description of the Drawings

[0019] [Figure 1] X-ray diffraction patterns of the positive electrode active material samples obtained in Example 1 and Comparative Example 1. [Diagram 2] X-ray diffraction patterns of the (003) plane of the positive electrode active material samples obtained in Example 1 and Comparative Example 1. [Diagram 3] X-ray diffraction patterns of the (104) plane of the positive electrode active material samples obtained in Example 1 and Comparative Example 1.

Modes for Carrying Out the Invention

[0020] Hereinafter, the present invention will be described based on preferred embodiments. The method for producing a positive electrode active material for a lithium secondary battery of the present invention is characterized by calcining a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and, as necessary, an M source. In other words, the method for producing a positive electrode active material for a lithium secondary battery of the present invention basically comprises the following raw material mixture preparation step and firing step, and thereby makes it possible to industrially advantageously obtain a positive electrode active material for a lithium secondary battery that can be imparted with excellent cycle characteristics. Raw material mixture preparation step: a step of preparing a raw material mixture by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and, as necessary, an M source. Firing step: a step of firing the raw material mixture prepared in the raw material mixture preparation step to obtain a positive electrode active material for a lithium secondary battery.

[0021] (Raw material mixture preparation process) The raw material mixture preparation step is a step of preparing a raw material mixture by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and, if necessary, an M source. That is, the raw material mixture preparation step is a step of preparing a raw material mixture by mixing a nickel source, a manganese source, a cobalt source, a lithium source, and lithium tungstate as essential raw materials, and further mixing an M source as necessary. M is one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K.

[0022] In the raw material mixture preparation step, the nickel source, manganese source, cobalt source and M source may be, for example, hydroxides, oxides, carbonates, nitrates, sulfates, organic acid salts and the like of nickel, manganese, cobalt and the M element. The nickel source, manganese source, cobalt source and the M source added as necessary have an average particle size of 0.50 to 100 μm, preferably 1.0 to 80.0 μm, in terms of the 50% volume cumulative particle size (D50) determined by a laser diffraction / scattering method.

[0023] In the raw material mixture preparation step, the nickel source, the manganese source, and the cobalt source may be a composite compound containing nickel atoms, manganese atoms, and cobalt atoms. Examples of the composite compound containing nickel atoms, manganese atoms, and cobalt atoms include composite oxides, composite hydroxides, composite oxyhydroxides, and composite carbonates containing nickel atoms, manganese atoms, and cobalt atoms. Among these, the nickel source, the manganese source, and the cobalt source are preferably composite hydroxides containing nickel atoms, manganese atoms, and cobalt atoms in that they provide higher cycle characteristics.

[0024] In the raw material mixture preparation step, the nickel source, the manganese source and the cobalt source may be mixed composite particles of a nickel compound, a manganese compound and a cobalt compound.

[0025] A known method can be used to prepare the composite compound containing nickel atoms, manganese atoms, and cobalt atoms. For example, in the case of a composite hydroxide, it can be prepared by a coprecipitation method. Specifically, a composite hydroxide can be coprecipitated by mixing an aqueous solution containing a predetermined amount of nickel atoms, cobalt atoms, and manganese atoms, an aqueous solution of a complexing agent, and an aqueous solution of an alkali (see JP-A-10-81521, JP-A-10-81520, JP-A-10-29820, JP-A-2002-201028, etc.). For example, in the case of a composite carbonate, a method of reacting a solution (Liquid A) containing nickel ions, manganese ions, and cobalt ions with a solution (Liquid B) containing carbonate ions or hydrogen carbonate ions in a reaction vessel (Japanese Patent Laid-Open No. 2009-179545) can be mentioned, or a method of reacting a solution (Liquid A) containing a nickel salt, manganese salt, and cobalt salt with a solution (Liquid B) containing a metal carbonate or metal hydrogen carbonate can be added to a solution (Liquid C) containing the same anion as the anion of the nickel salt, manganese salt, and cobalt salt in Liquid A and the same anion as the anion of the metal carbonate or metal hydrogen carbonate in Liquid B (Japanese Patent Laid-Open No. 2009-179544). The composite compound containing nickel atoms, manganese atoms, and cobalt atoms may be a commercially available product.

[0026] The mixed composite particles containing a nickel compound, a manganese compound and a cobalt compound can be prepared by a known method. For example, a slurry containing nickel compound particles, manganese compound particles, and cobalt compound particles can be pulverized using a bead mill or the like, and then spray-dried (JP Patent Publication No. 2012-206929), to obtain a mixed composite containing a nickel compound, a manganese compound, and a cobalt compound. The mixed composite particles containing a nickel compound, a manganese compound, and a cobalt compound may be a commercially available product.

[0027] In the raw material mixture preparation step, the composite compound containing nickel atoms, manganese atoms and cobalt atoms or the mixed composite particles containing a nickel compound, a manganese compound and a cobalt compound as the nickel source, manganese source and cobalt source have an average particle size of 0.50 to 30.0 μm, preferably 1.0 to 25.0 μm, as calculated as a 50% volume cumulative particle size (D50) determined by a laser diffraction / scattering method.

[0028] In the raw material mixture preparation step, the mixing ratio of the nickel source, manganese source, cobalt source and M source is appropriately selected depending on the composition ratio of nickel, manganese, cobalt and M in the lithium nickel manganese cobalt composite oxide to be produced, but is preferably selected from the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y satisfies 0.30 ≦ y < 1.00, z satisfies 0 < z ≦ 0.50, t satisfies 0 < t ≦ 0.50, p satisfies 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) It is a mixing ratio to form a lithium nickel manganese cobalt composite oxide represented by

[0029] In the raw material mixture preparation step, the lithium source is not particularly limited as long as it is a lithium compound usually used as a raw material for producing a lithium cobalt composite oxide, but lithium compounds other than lithium tungstate, such as lithium oxides, hydroxides, carbonates, nitrates, sulfates, and organic acid salts, are preferred.

[0030] In the raw material mixture preparation step, the average particle size of the lithium source is not particularly limited, and generally available ones can be used. For example, particle sizes in the range of 1 to 100 μm are common.

[0031] In the raw material mixture preparation step, the mixing ratio of the lithium source is preferably such that the molar ratio of Li atoms to the total number of moles of Ni atoms, Mn atoms, Co atoms, and M atoms in terms of atoms in the nickel source, manganese source, cobalt source, and M source (Li / (Ni + Mn + Co + M)) is 0.98 to 1.20, and particularly preferably 1.00 to 1.10. When the mixing ratio of the lithium source is within the above range, it is possible to increase the amount of lithium involved in the battery reaction while suppressing the amount of lithium present as residual alkali in the positive electrode active material for a lithium secondary battery.

[0032] In the raw material mixture preparation step, examples of lithium tungstate include LiWO3, Li2WO4, Li2W2O7, Li4WO5, Li6WO6, Li2W4O 13 , Li2W5O 16Alternatively, Li6W2O9 or a mixture thereof may be used, but Li2WO4 is preferred in that the particle size can be easily adjusted by pulverization.

[0033] In the raw material mixture preparation step, the average particle size of lithium tungstate is preferably 100.0 μm or less, more preferably 0.01 to 80.0 μm, as a particle size at 50% volumetric accumulation (D50) determined by a laser diffraction / scattering method using ethanol as a solvent. When the average particle size of lithium tungstate is within the above range, it becomes possible to uniformly mix lithium tungstate into the raw material mixture.

[0034] The lithium tungstate may be an aggregate in which primary particles are aggregated to form secondary particles. When the lithium tungstate is an aggregate, the primary particle diameter of the lithium tungstate is preferably 80.0 μm or less, preferably 0.001 to 60.0 μm, as the average particle diameter of the primary particles determined from a scanning electron microscope (SEM) photograph, from the viewpoint of uniformly mixing the lithium tungstate in the raw material mixture.

[0035] The average particle size of the primary particles was determined by randomly extracting 30 particles from SEM observation, measuring the short diameter and long diameter of each particle, calculating half the sum of the two, and averaging the measurements of the 30 particles to obtain the average particle size.

[0036] In the raw material mixture preparation step, the amount of lithium tungstate mixed is an amount such that the amount (mol) of W in atomic terms is 0.01 to 5.00 mol%, preferably 0.02 to 4.50 mol%, relative to the total amount (mol) of Ni, Mn, Co, and M in atomic terms in the nickel source, manganese source, cobalt source, and M source. By mixing the amount of lithium tungstate in the above range, it becomes possible to achieve both initial capacity and cycle characteristics within preferred ranges.

[0037] In the raw material mixture preparation step, the nickel source, the manganese source, the cobalt source, the lithium source, the lithium tungstate, and the M source can be mixed by either a dry method or a wet method, but the dry method is preferred because of ease of production.

[0038] In the case of dry mixing, it is preferable to use a mechanical means so that the raw materials are mixed uniformly. Examples of mixing devices include high-speed mixers, super mixers, turbosphere mixers, Eirich mixers, Henschel mixers, Nauta mixers, ribbon blenders, V-type mixers, conical blenders, jet mills, cosmomixers, paint shakers, bead mills, ball mills, etc. At the laboratory level, household mixers and laboratory mills are sufficient.

[0039] In the case of wet mixing, it is preferable to use a media mill as a mixing device, since it is possible to prepare a slurry in which each raw material is uniformly dispersed. In addition, it is preferable to spray-dry the slurry after the mixing process, from the viewpoint of obtaining a raw material mixture with excellent reactivity and in which each raw material is uniformly dispersed.

[0040] (Firing process) The calcination step is a step of calcining the raw material mixture prepared in the raw material mixture preparation step. By carrying out this calcination, a positive electrode active material for lithium secondary batteries can be obtained.

[0041] In the calcination step, the calcination temperature is 600 to 1000° C., preferably 650 to 950° C. The reason for this is that if the calcination temperature is less than 600° C., the reaction is insufficient and a large amount of unreacted lithium tends to remain, whereas if the calcination temperature exceeds 1000° C., the lithium nickel manganese cobalt composite oxide that has been produced tends to decompose.

[0042] In the firing process, the firing time is not critical. Usually, if it is 3 hours or more, preferably 5 to 30 hours, more preferably 6.5 to 29 hours, a lithium secondary battery positive electrode active material with satisfactory performance can be obtained. The firing atmosphere is preferably an atmospheric atmosphere such as air or oxygen gas.

[0043] Also, in the firing process, the firing may be performed in multiple stages. By firing in multiple stages, a lithium secondary battery positive electrode active material that can impart even more excellent cycle characteristics can be obtained. When firing in multiple stages, it is fired at 600 to 800 °C, preferably 650 to 800 °C, for 1 to 10 hours, and then without cooling, the temperature is raised to 800 to 1000 °C, preferably 800 to 950 °C, so as to reach a higher temperature, and it is preferably fired at that temperature for 5 to 30 hours, more preferably 6.5 to 29 hours.

[0044] In the method for producing a positive electrode active material for a lithium secondary battery of the present invention, after the firing process, pulverization, classification, granulation, etc. may be performed as necessary.

[0045] The positive electrode active material for a lithium secondary battery obtained by performing the method for producing a positive electrode active material for a lithium secondary battery of the present invention preferably has the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y represents 0.30 ≦ y < 1.00, z represents 0 < z ≦ 0.50, t represents 0 < t ≦ 0.50, p represents 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) It contains lithium nickel manganese cobalt composite oxide particles represented by the formula and W atoms.

[0046] In the formula of general formula (1), x satisfies 0.98 ≤ x ≤ 1.20. Preferably, x satisfies 1.00 ≤ x ≤ 1.10 in terms of increasing the initial capacity. Also, in the formula of general formula (1), y satisfies 0.30 ≤ y < 1.00. Preferably, y satisfies 0.50 ≤ y ≤ 0.95 in terms of achieving favorable initial capacity and cycle characteristics, and particularly preferably 0.60 ≤ y ≤ 0.90. Further, in the formula of general formula (1), z satisfies 0 < z ≤ 0.50. Preferably, z satisfies 0.025 ≤ z ≤ 0.45 in terms of excellent safety. Also, t satisfies 0 < t ≤ 0.50. Preferably, t satisfies 0.025 ≤ t ≤ 0.45 in terms of excellent safety. y + z + t + p = 1. Preferably, (y / z) > 1, particularly preferably (y / z) ≥ 1.5, and more preferably 3 ≤ (y / z) ≤ 38.

[0047] In the formula, M is a metal element that is incorporated into the lithium nickel manganese cobalt composite oxide represented by general formula (1) as needed for the purpose of improving battery performance such as cycle characteristics and safety. Examples of M include one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. In the formula of general formula (1), p satisfies 0 ≤ p ≤ 0.050, preferably 0.0001 ≤ p ≤ 0.045.

[0048] The positive electrode active material for a lithium secondary battery obtainable by carrying out the method for producing a positive electrode active material for a lithium secondary battery of the present invention preferably contains a lithium nickel manganese cobalt composite oxide represented by general formula (1) and W atoms. However, the state of existence of W atoms in the lithium nickel manganese cobalt composite oxide represented by general formula (1) according to the method for producing a positive electrode active material for a lithium secondary battery of the present invention is not clear.

[0049] However, for example, Comparative Example 1 in the present specification is a positive electrode active material for lithium secondary batteries obtained in the same manner as in Example 1 in the present specification, except that lithium tungstate was not mixed. When comparing the X-ray diffraction pattern ((b) in FIG. 1) of the positive electrode active material for lithium secondary batteries obtained in Comparative Example 1 with the X-ray diffraction pattern ((a) in FIG. 1) of the positive electrode active material for lithium secondary batteries obtained in Example 1, it can be confirmed that the diffraction peaks ((a) in FIG. 2 and (a) in FIG. 3) derived from the (003) and (104) planes in the latter are shifted to the lower angle side than the diffraction peaks ((b) in FIG. 2 and (b) in FIG. 3) derived from the (003) and (104) planes in the former. Therefore, it is considered that W atoms are present in a solid solution state at least inside the particles of the lithium nickel manganese cobalt composite oxide.

[0050] The average particle size of the positive electrode active material for lithium secondary batteries obtained by carrying out the method for producing a positive electrode active material for lithium secondary batteries of the present invention is 0.50 to 30.0 μm, preferably 1.0 to 25.0 μm, and particularly preferably 1.5 to 20.0 μm, as a particle size at 50% volume (D50) determined by a laser diffraction / scattering method. The BET specific surface area of ​​the positive electrode active material for lithium secondary batteries obtained by carrying out the method for producing a positive electrode active material for lithium secondary batteries of the present invention is preferably 0.05 to 2.00 m. 2 / g, particularly preferably 0.15 to 1.00 m 2 When the average particle size or BET specific surface area of ​​the positive electrode active material for lithium secondary batteries obtained by carrying out the method for producing a positive electrode active material for lithium secondary batteries of the present invention is within the above-mentioned range, the preparation and coating properties of the positive electrode mixture become easy, and furthermore, an electrode with high packing properties can be obtained.

[0051] In the method for producing a positive electrode active material for a lithium secondary battery of the present invention, lithium tungstate is mixed into the raw material before producing the lithium nickel manganese cobalt composite oxide, instead of the lithium nickel manganese cobalt composite oxide, thereby obtaining a positive electrode active material for a lithium secondary battery having excellent cycle characteristics. In the method for producing a positive electrode active material for a lithium secondary battery of the present invention, a composite compound containing nickel atoms, manganese atoms, and cobalt atoms is used as the raw material nickel source, manganese source, and cobalt source, thereby enhancing the effect of obtaining a positive electrode active material for a lithium secondary battery having excellent cycle characteristics.

[0052] In the method for producing the positive electrode active material for lithium secondary batteries of the present invention, for example, large particles having an average particle size of 7.5 to 30.0 μm, preferably 8.0 to 25.0 μm, particularly preferably 8.5 to 20.0 μm, and small particles smaller than the large particles, that is, small particles having an average particle size of 0.5 to 7.5 μm, preferably 1.0 to 7.0 μm, particularly preferably 1.5 to 6.5 μm, may be separately produced, and then the obtained large particles and small particles may be mixed at a predetermined mixing ratio. The positive electrode active material for lithium secondary batteries obtained by performing the step of mixing the large particles and the small particles at a predetermined mixing ratio can be a positive electrode active material for lithium secondary batteries that can provide excellent cycle characteristics while further increasing the discharge capacity per volume.

[0053] The mixing ratio of the large particles to the small particles is preferably 7:13 to 19:1 by mass, and more preferably 1:1 to 9:1 by mass. 2 The compression density when compressed is 2.7g / cm 3 or more, preferably 2.8 to 3.3 g / cm 3 , particularly preferably 2.9 to 3.3 g / cm 3 This is preferable from the viewpoint of further improving the discharge capacity per volume.

[0054] As a method for producing large particles, for example, in the above-mentioned raw material mixture preparation step, composite compounds containing nickel atoms, manganese atoms, and cobalt atoms, each having a volume-integrated 50% particle diameter (D50) of 7.5 to 100 μm, preferably 8.0 to 80 μm, as the nickel source, manganese source, and cobalt source determined by a laser diffraction / scattering method, are used, and then the above-mentioned firing step is carried out, thereby obtaining large particles. As for a method for producing small particles, for example, in the above-mentioned raw material mixture preparation step, composite compounds containing nickel atoms, manganese atoms, and cobalt atoms, each having a 50% volume cumulative particle diameter (D50) of 0.5 to 7.5 μm, preferably 1.0 to 7.0 μm, as the nickel source, manganese source, and cobalt source determined by a laser diffraction / scattering method, are used, and then the above-mentioned firing step is carried out, thereby obtaining small particles.

[0055] The positive electrode active material for lithium secondary batteries obtained by the method for producing a positive electrode active material for lithium secondary batteries of the present invention is useful in that it can impart excellent cycle characteristics when used as a positive electrode active material for lithium secondary batteries. EXAMPLES

[0056] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0057] (Examples 1 to 2) (Raw material mixture preparation process) Lithium carbonate (average particle size 5.7 μm), nickel manganese cobalt composite hydroxide (Ni:Mn:Co=6:2:2 (molar ratio), average particle size 3.8 μm or 12.1 μm), and lithium tungstate (Li2WO4, average particle size 7.9 μm) were weighed out and thoroughly mixed in a household mixer to obtain a raw material mixture in which the molar ratio of Li / (Ni+Mn+Co) and the mixed amount of lithium tungstate were values ​​shown in Table 1. Note that, for the nickel manganese cobalt composite hydroxide used in Example 1, a commercially available product with an average particle size of 3.8 μm and an average particle size of 12.1 μm was used in Example 2. (Firing Process) Subsequently, the obtained raw material mixture was fired in an alumina crucible at 700 °C for 2 hours, followed by firing at 850 °C for 10 hours in an air atmosphere. After the firing was completed, the fired product was pulverized and classified to obtain a positive electrode active material sample. As a result of measuring the positive electrode active material sample obtained in Example 1 by X-ray diffraction method (XRD), diffraction peaks derived from lithium nickel manganese cobalt composite oxide were confirmed (see (a) in Fig. 1). Also, it was confirmed that the diffraction peaks derived from the (003) plane and the (104) plane were shifted to the low angle side (see (a) in Fig. 2 and (a) in Fig. 3).

[0058] (Comparative Example 1) (Raw Material Mixture Preparation Process) Lithium carbonate (average particle diameter 5.7 μm) and nickel manganese cobalt composite hydroxide (Ni:Mn:Co = 6:2:2 (molar ratio), average particle diameter 3.8 μm) were weighed and sufficiently mixed using a household mixer to obtain a raw material mixture in which the molar ratio of Li / (Ni + Mn + Co) was the value shown in Table 1. Note that a commercially available nickel manganese cobalt composite hydroxide was used. (Firing Process) Subsequently, the obtained raw material mixture was fired in an alumina crucible at 700 °C for 2 hours, followed by firing at 850 °C for 10 hours in an air atmosphere. After the firing was completed, the fired product was pulverized and classified to obtain a positive electrode active material sample. As a result of measuring the obtained positive electrode active material sample by XRD, diffraction peaks derived from lithium nickel manganese cobalt composite oxide were confirmed (see (b) in Fig. 1). Also, the obtained positive electrode active material sample was spherical lithium nickel manganese cobalt composite oxide (LiNi 0.6 Mn 0.2 Co 0.2 O2).

[0059] For the positive electrode active material samples obtained in Examples 1 to 2 and Comparative Example 1, the following physical properties were measured, and the results are shown in Table 1. <Average Particle Diameter> Determined by laser diffraction / scattering method. <BET Specific Surface Area> Determined by BET method. <Pressure density> 2.25 g of the positive electrode active material sample was weighed and placed in a biaxial molding machine with a diameter of 1.5 cm, and pressurized to 0.65 tonf / cm 2 With the pressure applied for one minute, the height of the compressed product was measured, and the compressed density of the positive electrode active material sample was calculated from the apparent volume of the compressed product calculated from the height and the weighed mass of the positive electrode active material sample.

[0060] [Table 1]

[0061] Regarding *1 in Table 1, the amount of lithium tungstate mixed was calculated as the percentage of the amount (moles) of W in atomic terms to the total amount (moles) of Ni, Mn, and Co in atomic terms.

[0062] The battery performance test was carried out as follows. <Preparation of lithium secondary battery 1> A positive electrode agent was prepared by mixing 94% by mass of the positive electrode active material samples obtained in Examples 1 and 2 and Comparative Example 1, 3% by mass of graphite powder, and 3% by mass of polyvinylidene fluoride, and this was dispersed in N-methyl-2-pyrrolidinone to prepare a kneaded paste. The kneaded paste was applied to aluminum foil, dried, pressed, and punched into a disk with a diameter of 15 mm to obtain a positive electrode plate.

[0063] Using this positive electrode plate, a coin-type lithium secondary battery was produced using each component such as a separator, negative electrode, positive electrode, current collector, mounting metal fittings, external terminals, and electrolyte, etc. Metallic lithium foil was used for the negative electrode, and 1 mole of LiPF6 dissolved in 1 liter of a 1:1 mixture of ethylene carbonate and methyl ethyl carbonate was used for the electrolyte.

[0064] <Battery performance evaluation 1> The coin-type lithium secondary batteries thus fabricated were then operated at room temperature under the following test conditions, and the following battery performance evaluations were performed. The results are shown in Table 2. (1) Test conditions for cycle characteristic evaluation First, the battery was charged to 4.3 V at 0.5 C over 2 hours, and then constant current / constant voltage charging (CCCV charging) was performed to hold the voltage at 4.3 V for 3 hours. Then, the battery was charged and discharged at a constant current (CC discharge) of 0.2 C or 1.0 C to 2.7 V. This cycle was repeated for a total of 30 cycles, and the discharge capacity was measured after each cycle. The battery was CC discharged at 0.2 C for the 1st, 2nd, 10th, 20th, and 30th cycles, and at 1.0 C for the other cycles. (2) Initial charge capacity, initial discharge capacity (per weight of active material) The charge capacity and discharge capacity in the first cycle in the cycle characteristic evaluation were defined as the initial charge capacity and the initial discharge capacity. (3) Discharge capacity at 30th cycle (per weight of active material) The discharge capacity at the 30th cycle in the cycle characteristic evaluation was defined as the 30th cycle discharge capacity. (4) Capacity maintenance rate The capacity retention rate was calculated from the discharge capacity (per active material weight) at the 1st cycle and the 30th cycle in the cycle characteristic evaluation according to the following formula. Capacity retention rate (%) = (discharge capacity at 30th cycle / discharge capacity at 1st cycle) x 100 (5) Energy density maintenance rate The energy density retention rate was calculated from the Wh capacity (per active material weight) during discharge in each of the 1st and 30th cycles in the cycle characteristic evaluation, using the following formula. Energy density retention rate (%) = (30th cycle discharge Wh capacity / 1st cycle discharge Wh capacity) x 100

[0065] [Table 2]

[0066] It can be seen from Table 2 that the lithium secondary batteries using the positive electrode active material samples containing W atoms (Examples 1 and 2) have improved capacity retention and energy density retention rates compared to the lithium secondary battery using the positive electrode active material sample not containing W atoms (Comparative Example 1). In other words, it was confirmed that the lithium secondary batteries using the positive electrode active material sample containing W atoms have excellent cycle characteristics.

[0067] <Preparation of lithium secondary battery 2> The positive electrode active material samples obtained in Examples 1 and 2 were thoroughly mixed in a household mixer to prepare mixtures having the compositions shown in Table 3, which were used as positive electrode active material samples. In addition, the pressed density of the obtained positive electrode active material samples was measured, and the results are shown in Table 3.

[0068] [Table 3]

[0069] A positive electrode material was prepared by mixing 94% by mass of the positive electrode active material sample, 3% by mass of graphite powder, and 3% by mass of polyvinylidene fluoride, and this was dispersed in N-methyl-2-pyrrolidinone to prepare a kneaded paste. The kneaded paste was applied to an aluminum foil, dried, pressed, and punched into a disk with a diameter of 15 mm to obtain a positive electrode plate.

[0070] Using this positive electrode plate, a coin-type lithium secondary battery was produced using each component such as a separator, negative electrode, positive electrode, current collector, mounting metal fittings, external terminals, and electrolyte, etc. Metallic lithium foil was used for the negative electrode, and 1 mole of LiPF6 dissolved in 1 liter of a 1:1 mixture of ethylene carbonate and methyl ethyl carbonate was used for the electrolyte.

[0071] <Battery performance evaluation 2> Next, the prepared coin-type lithium secondary battery was operated at room temperature under the following test conditions, and the cycle characteristics, initial charge capacity, initial discharge capacity (per active material weight), 30th cycle discharge capacity (per active material weight), capacity retention rate, and energy density retention rate were evaluated in the same manner as in Battery Performance Evaluation 1, and further the following battery performance was evaluated. The results are shown in Table 4. (6) Discharge capacity per volume The discharge capacity per volume was calculated from the initial discharge capacity, the electrode density, and the ratio of the amount of active material in the coating agent according to the following formula. Discharge capacity per volume (mAh / cm 3 )=Initial discharge capacity (mAh / g) × Electrode density (g / cm 3 ) x 0.94 (proportion of active material in coating agent) The electrode density was calculated by measuring the mass and thickness of the electrode prepared from the measurement sample, and subtracting the thickness and mass of the current collector from the mass and thickness to obtain the density of the positive electrode material. The positive electrode material was a mixture of 94 mass % of the positive electrode active material sample, 3 mass % of graphite powder, and 3 mass % of polyvinylidene fluoride, and the pressing pressure during electrode preparation was 0.38 ton / cm in linear pressure.

[0072] [Table 4]

[0073] From Table 4, it was confirmed that mixture 1, which is a mixture of a positive electrode active material sample of large particles containing W atoms and a positive electrode active material sample of small particles containing W atoms, serves as a positive electrode active material for lithium secondary batteries that can increase the discharge capacity per volume while imparting excellent cycle characteristics.

Claims

1. A method for producing a positive electrode active material for a lithium secondary battery, comprising calcining a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium tungstate, and optionally an M source.

2. 2. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the nickel source, the manganese source and the cobalt source are composite compounds containing nickel atoms, manganese atoms and cobalt atoms.

3. The lithium tungstate is Li 2 WO 4 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein

4. 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the calcination is carried out at a temperature of 600 to 1000° C.

5. 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, further comprising the steps of: calcining at 600 to 800° C. for 1 to 10 hours; and then calcining at 800 to 1000° C. for 5 to 30 hours.

6. 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the amount of lithium tungstate mixed is an amount such that an amount of W in atomic terms is 0.01 to 5.00 mol % relative to the total amount of Ni, Mn, Co, and M in atomic terms in the nickel source, manganese source, cobalt source, and M source.

7. The positive electrode active material for a lithium secondary battery is represented by the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98≦x≦1.20, y represents 0.30≦y<1.00, z represents 0<z≦0.50, t represents 0<t≦0.50, p represents 0≦p≦0.05, and y+z+t+p=1.) 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, comprising the steps of:

8. A method for producing a positive electrode active material for a lithium secondary battery, comprising a step of mixing large particles having an average particle diameter of 7.5 to 30.0 μm obtained by the method for producing the positive electrode active material according to claim 1 or 2 with small particles having an average particle diameter of 0.5 to 7.5 μm obtained by the method for producing the positive electrode active material according to claim 1 or 2.

Citation Information

Patent Citations

  • Lithium nickel manganese cobalt based composite oxide for lithium secondary battery positive electrode material, positive electrode for lithium secondary battery using it, and lithium secondary battery

    JP2005025975A

  • Positive active material for lithium secondary battery, method of manufacturing the same, and lithium secondary battery

    JP2011023120A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and method for manufacturing the same

    JP2016024968A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, fluid dispersion used in producing the same, and production method thereof

    JP2016072071A

  • Lithium-nickel-cobalt-manganese containing composite oxide, material for positive electrode active material for lithium secondary battery, and methods for producing these

    WO2004092073A1